Whether or Not A Shunt is Placed in the Brain (Pre/Post Repair) for Patients with a Lumbar Meningocele and Hydrocephalus Undergoing a Lumbar Meningocele Procedure - Ali Abbas Hashim Almusawi (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study involves the important comparison in doing V-P shunt operation before surgical correction and repair to the neonates born with spinal dysraphism meningocele at the lumber region versus doing V-P shunt after repair of neural tube defect meningocele to avoid post operative (correction of neural tube defect) leaking cerebrospinal fluid and surgical wound infection.The study 50 newborn babies with hydrocephalus and spinal dysraphism meningocele.